Twinning Engineering of a CoCrFeMnNi High-Entropy Alloy. (May 2021) - Moon, Jongun; Bouaziz, Olivier; Kim, Hyoung Seop; Estrin, Yuri
Abstract: Deformation-induced twinning has been a notable example of overcoming the strength/ductility trade-off dilemma as a strengthening mechanism. By borrowing this concept from the area of TWIP steels, we designed a thermomechanical treatment for a CoCrFeMnNi high-entropy alloy to improve its mechanical characteristics. We used pre-straining at 77 K to introduce deformation-induced twins in the microstructure of the alloy, and then recovered it by annealing at 773 K, while avoiding recrystallization. The deformation-induced twins generated by pre-straining at 77 K were retained after this heat treatment, whilst partial recovery of dislocations occurred. As a result, the room-temperature mechanical properties of the alloy, including its strain hardening ability, were improved substantially. Graphical abstract: Image, graphical abstract